IMPLEMENTASI KAIDAH AL-YAQĪN LĀ YAZŪLU BI AL-SYAKK PADA SENGKETA AKAD DIGITAL DAN PEMBUKTIAN ELEKTRONIK DI INDONESIA - Nur Rizki Aulia; Raka Indra Purnama; Rifaldi Hidayat; Agus Rojak Samsudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of digital transactions in Indonesia has transformed the implementation of contracts while raising legal issues concerning the validity of digital contracts and the evidentiary value of electronic evidence in dispute resolution. This study aims to analyze the implementation of the legal maxim al-yaqīn lā yazūlu bi al-syakk (certainty is not overruled by doubt) in resolving disputes over digital contracts and its relevance to electronic evidence in Indonesia. This research employs a normative legal method using conceptual, statutory, and library research approaches. The data were collected from legislation, Islamic jurisprudence literature, books, and scholarly journals and analyzed using a qualitative descriptive method. The findings indicate that the legal maxim al-yaqīn lā yazūlu bi al-syakk provides a normative foundation that a digital contract supported by valid electronic evidence cannot be invalidated solely based on allegations or denial without sufficient proof. The validity of digital contracts in Islamic commercial law (fiqh muamalah) is recognized as long as the essential elements and legal requirements of a contract are fulfilled, including mutual consent, a clearly defined object, and a lawful purpose. Furthermore, the study demonstrates a strong alignment between the principle of legal certainty in Islamic law and the recognition of electronic evidence under Indonesian positive law. Therefore, this legal maxim remains relevant as a normative basis for resolving digital contract disputes while strengthening legal certainty and legal protection for parties involved in electronic transactions.